“Little Brown Brothers”: Height and the Philippine–American Colonial Encounter (1898–1946) - Lasco, Gideon; University (Archīum Ateneo, 2018)
Thisarticle looks at how scientific racism, biomedicine, public health, sports, and a nascent bureaucracy intersected in the making of height (human stature) as an important attribute of individuals and populations during the Philippine–American colonial encounter. In relation to the “tall” Americans, Filipinos were depicted and problematized as “short,” and the attention to children’s growth, the rise of sports, and the establishment of a bureaucracy all contributed to making height a measure of health and a parameter of inclusion (and exclusion) in various domains of society.KEYWORDS: HEIGHT • ANTHROPOMETRY • PUBLIC HEALTH • COLONIALISM • PHILIPPINES